PENEGAKKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 25/PUU-XIV/2016 - Roberts K (Ensiklopedia of Journal, 2023)
Abstract:On January 25 2017, the Constitutional Court (MK) issued Decision Number 25/PUU-XIV/2016. This decision basically states that the word "can" in Article 2 Paragraph (1) and Article 3 of Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning Eradication of Corruption Crimes (UU Tipikor) is contrary to the constitution and has no binding legal force. With the omission of the word "can", then automatically, a new person can be said to have violated Article 2 Paragraph (1) and Article 3 of the Corruption Law if the person's actions have caused real state losses, or losses with the nature of actual loss, and not again accommodate state losses that are still potential, or potential losses.Keywords: Law Enforcement, Corruption Crime, Constitutional Court Decision.